Gefitinib Results in Robust Host-Directed Immunity Against Salmonella Infection Through Proteo-Metabolomic Reprogramming - Sadhu, Srikanth; Rizvi, Zaigham Abbas; Pandey, Ramendra Pati; Dalal, Rajdeep; Rathore, Deepak Kumar; Kumar, Bhoj; Pandey, Manitosh; Kumar, Yashwant; Goel, Renu; Maiti, Tushar K.; Johri, Atul Kumar; Tiwari, Ashutosh; et al. (Frontiers in Immunology, 2021)
The global rise of antibiotic-resistant strains of Salmonella has necessitated the development of alternative therapeutic strategies. Recent studies have shown that targeting host factors may provide an alternative approach for the treatment of intracellular pathogens. Host-directed therapy (HDT) modulates host cellular factors that are essential to support the growth and survival of the intracellular pathogens. In the current study, we identified Gefitinib as a potential host directed therapeutic drug against Salmonella. Further, using the proteome analysis of Salmonella-infected macrophages, we identified EGFR, a host factor, promoting intracellular survival of Salmonella via mTOR-HIF-1α axis. Blocking of EGFR, mTOR or HIF-1α inhibits the intracellular survival of Salmonella within the macrophages and in mice. Global proteo-metabolomics profiling indicated the upregulation of host factors predominantly associated with ATP turn over, glycolysis, urea cycle, which ultimately promote the activation of EGFR-HIF1αsignalling upon infection. Importantly, inhibition of EGFR and HIF1α restored both proteomics and metabolomics changes caused by Salmonella infection. Taken together, this study identifies Gefitinib as a host directed drug that holds potential translational values against Salmonella infection and might be useful for the treatment of other intracellular infections.